2014
DOI: 10.1155/2014/164391
|View full text |Cite|
|
Sign up to set email alerts
|

Downregulation ofMDR1Gene by Cepharanthine Hydrochloride Is Related to the Activation of c-Jun/JNK in K562/ADR Cells

Abstract: The purpose of the study was to determine the signal transduction mechanism of cepharanthine hydrochloride (CH) on reversing tumor multidrug resistance. RT-PCR and Western blot analysis were used to determine the effects of CH on the expression of MDR1 mRNA and P-glycoprotein in K562/ADR cells when CH was used alone and combined with SP600125, a JNK inhibitor, to explore the effects of CH on JNK pathway. Western blot analysis was used to determine the effects of CH on c-Jun protein expression and phosphorylati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 25 publications
2
19
0
Order By: Relevance
“…It exhibits antimalarial, anti-viral, anti-inflammatory, anti-metastatic, and anti-cancer activities in various cell lines and animal models [772,[774][775][776]. Among its anti-cancer activities, CEP exhibits multiple pharmacological actions, including apoptosis and radiation sensitization, inhibition of angiogenesis and metastasis, and reversing MDR [776][777][778][779][780][781][782][783][784][785][786][787][788][789].…”
Section: Cepharanthine (Cep)mentioning
confidence: 99%
See 1 more Smart Citation
“…It exhibits antimalarial, anti-viral, anti-inflammatory, anti-metastatic, and anti-cancer activities in various cell lines and animal models [772,[774][775][776]. Among its anti-cancer activities, CEP exhibits multiple pharmacological actions, including apoptosis and radiation sensitization, inhibition of angiogenesis and metastasis, and reversing MDR [776][777][778][779][780][781][782][783][784][785][786][787][788][789].…”
Section: Cepharanthine (Cep)mentioning
confidence: 99%
“…Targeting P-gp using P-gp inhibitors is one of the main strategies to reverse MDR, and cepharanthine hydrochloride (CEH), a salt form of CEP, is suggested to be a potent P-gp inhibitor [779]. CEH exhibits MDR reversal potency in various cancer cells [779][780][781]788]. CEH can reverse MDR-mediated cisplatin resistance in esophageal squamous cell carcinoma [780].…”
Section: Cepharanthine (Cep)mentioning
confidence: 99%
“…The c-Jun N-terminal kinases (JNK) belong to the mitogen-activated protein kinase (MAPK) family (12). There are three JNK isoforms in mammals, JNK1, JNK2 and JNK3, which are encoded by the MAPK8, MAPK9 and MAPK10 genes, respectively (13).…”
Section: Introductionmentioning
confidence: 99%
“…The JNK signaling pathway has been reported to be involved in cellular proliferation, apoptosis and differentiation, and tumor cell migration (16,17). Increasing evidence has indicated that JNK activity serves an important role in the development of chemoresistance and is associated with MRP1 expression (12)(13)(14)(15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…BioMed Research International has retracted the article titled “Downregulation of MDR1 Gene by Cepharanthine Hydrochloride Is Related to the Activation of c-Jun/JNK in K562/ADR Cells.” [1]. β -Actin loading controls in the Western Blots were duplicated.…”
mentioning
confidence: 99%